Determination of doxazosin in different matrices: a review - Shrivastava, Alankar; Jain, Manali; Varshneya, Rakhee (International Journal of Advanced Chemistry, 2014)
Doxazosin mesylate is used in the management of hypertension and benign prostatic hyperplasia. It is one of the important alpha one adrenoreceptor blocker. Alpha one adrenoreceptor blockers are most preferred therapy for symptomatic relief of benign prostatic hyperplasia. In this review analytical methods for the determination of doxazosin in different matrices are discussed. Analytical methods are classified in to spectrophotometry, chromatography and electroanalytical methods. This literature is also focused on advantages, disadvantages of different analytical methods. This review article is an attempt to provide information to the scientists engaged in research related to doxazosin. Keywords: Benign Prostatic Hyperplasia, Doxazosin Mesylate, Analytical Methods, Spectrophotometry, Chromatography, Electro analytical Methods.